Pengaruh Tata Ruang Kantor terhadap Kenyamanan Pegawai dan Nasabah di Kantor Bank PERMATA Jl. Panglima Sudirman Surabaya - Albani, Avisienna; Paryoko, Vijar Galax Putra Jagat (Universitas Medan Area, 2025)
Spatial planning in offices can affect the comfort of the occupants, so good spatial planning is needed. The aim of this research is to find out whether the Bank Permata Panglima Sudirman office, Surabaya has implemented good spatial planning for employees and customers and to find out the impact on its residents. This research method uses descriptive qualitative using primary data collected through observation, documentation and interviews and is continued by taking literature studies in the form of books, journals and articles to analyze the influence of the Permata Bank office layout on residents. The results of the research show that the office layout of Bank Permata Panglima Sudirman, Surabaya is quite good because it has implemented the theory of good office space planning through journals or books so that it has a positive effect on employee performance and increases the attraction for bank customers.